2013
DOI: 10.3126/njh.v8i1.8333
|View full text |Cite
|
Sign up to set email alerts
|

Current Scenario of Heart Diseases in Nepal: At a glance

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…Hospital-based prevalence study of NCDs in 31 hospitals across Nepal found that 36.5% admitted patients were NCDs, of which 38 % were the CVD 11 . Different hospital based studies show that the prevalence of CVD was 31% 12 , 5 to 40% based on the data of the cardiac camps of three consecutive years (2008-2011) throughout Nepal 13 . Another hospital based shows that the majority of the deaths were neonates, less than one month accounted for 12.9% and over 60 years accounted for 36.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital-based prevalence study of NCDs in 31 hospitals across Nepal found that 36.5% admitted patients were NCDs, of which 38 % were the CVD 11 . Different hospital based studies show that the prevalence of CVD was 31% 12 , 5 to 40% based on the data of the cardiac camps of three consecutive years (2008-2011) throughout Nepal 13 . Another hospital based shows that the majority of the deaths were neonates, less than one month accounted for 12.9% and over 60 years accounted for 36.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Combined data from different sources indicate the problem is common. [3] A hospital based prevalence of non-communicable disease from different hospitals across the country found cardiovascular disease as the most common (40%) among non-communicable diseases. [4] Risk factors for this disease such as hypertension, dyslipidemia, diabetes, smoking, and obesity are controllable.…”
Section: Introductionmentioning
confidence: 99%
“…10,11,12 As the severity of MS increases, the incidence of thrombus formation in LA and LAA increases. 8 The present study evaluated the cases of severe MS for the presence of LAA clot using TEE.…”
Section: Discussionmentioning
confidence: 99%